GCLM lactylation mediated by ACAT2 promotes ferroptosis resistance in KRASG12D-mutant cancer - Chen, Yubin; Yan, Qian; Ruan, Shiye; Cui, Jinwei; Li, Zhenchong; Zhang, Zhongyan; Yang, Jiayu; Fang, Jike; Liu, SiYang; Huang, Shanzhou; Hou, Baohua; Zhang, Chuanzhao (Cell reports, 2025)
KRAS mutations drive tumorigenesis, but their role in ferroptosis regulation remains unclear. Here, we construct wild-type KRAS (KRASWT) and KRASG12D-mutant cancer cells and demonstrate that G12D-mutant cells exhibit increased viability and reduced ferroptosis upon RSL3 or erastin treatment. These cells show diminished lipid peroxidation and mitochondrial damage, indicating ferroptosis resistance. KRASG12D activates MEK/ERK signaling to phosphorylate LDHA, enhancing glycolysis and lactate production. Exogenous lactate supplementation similarly protects WT cells from ferroptosis. Mechanistically, G12D-mutation-derived lactate induces glutamate-cysteine ligase (GCL) modifier (GCLM) lactylation, a process catalyzed by acetyl-coenzyme A (CoA) acetyltransferase 2 (ACAT2). Inhibition of GCLM lactylation either through the mutation of the lactylation site or by knockdown of ACAT2 diminished the enzymatic activity of GCL and suppressed glutathione synthesis. Importantly, ACAT2 depletion overcomes ferroptosis resistance in KRASG12D-mutant tumors in vivo. Our findings reveal a KRASG12D-driven metabolic adaptation linking GCLM lactylation to ferroptosis resistance, proposing ACAT2 inhibition as a therapeutic strategy for KRAS-mutant cancers.
Online verfügbar: 9. Juni 2025, Artikelversion: 9. Juni 2025
Im Titel ist "G12D" hochgestellt
Gesehen am 25.09.2025